High far infrared glasses frame and manufacturing method thereof

By using composite materials of polyether etherketone, graphene and iron in the glasses frame, the problems of uneven distribution and low release efficiency of far infrared materials in traditional glasses are solved, and efficient far infrared release and good wearing experience are achieved.

CN119708807APending Publication Date: 2025-03-28HENGFENG EYEWEAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411776566.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional glasses are difficult to achieve uniform distribution and efficient release of far infrared materials in the glasses frame, resulting in increased weight, reduced flexibility and reduced wear comfort, affecting the application of far infrared materials.

Method used

Polyether ether ketone (PEEK) is used as the matrix material, combining graphene and iron elements, and through the mixing of graphene and iron, nanoparticle treatment and composite with PEEK materials, the uniform distribution and efficient release of far-infrared materials in the glasses frame are achieved.

Benefits of technology

It achieves stable far-infrared release, maintains the lightweight and durable properties of PEEK materials, improves the far-infrared emission performance, promotes local blood circulation and metabolism around the wearer's eyes, and provides a healthier and more comfortable wearing experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708807A_ABST
    Figure CN119708807A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of glasses manufacturing, in particular to a high far infrared glasses frame and a manufacturing method thereof. The high far infrared glasses frame comprises the following components in parts by mass: 75-94 parts of polyether-ether-ketone, 5-20 parts of graphene and 1-5 parts of an iron element, and a manufacturing method of the high far infrared glasses frame comprises the following steps: in a dehumidification environment, uniformly mixing graphene nanoparticles with an iron salt solution, carrying out melt blending with the polyether-ether-ketone to obtain a composite material, carrying out extrusion granulation, and carrying out injection molding on the particles by using a mold to obtain the high far infrared glasses frame. And the high far infrared glasses frame is obtained. According to the invention, polyether-ether-ketone (PEEK) is adopted as a base material, and the excellent performance of graphene is utilized, and the far infrared emission enhancement effect of iron is combined, so that stable far infrared emission is realized; through mixing of graphene and iron, nanoparticle treatment and compounding with the PEEK material, the characteristics of portability and durability of the PEEK material are maintained, the far infrared emission performance is improved, and local blood circulation and metabolism around the eyes of a wearer are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glasses manufacturing, and in particular to a high-far infrared glasses frame and a manufacturing method thereof. Background Art

[0002] Traditional eyewear design focuses on correcting vision, protecting eyes and being a fashion accessory, with less consideration given to the added value of health promotion. Far-infrared materials such as bamboo charcoal, ceramics and graphene are widely used in the medical and beauty fields because of their ability to release far-infrared rays. These materials can relieve muscle tension and improve blood circulation by promoting human cell activity.

[0003] However, it is difficult to achieve uniform distribution and efficient release of far-infrared materials in glasses frames using traditional methods, and traditional integration methods also increase the weight of glasses, while reducing their flexibility and wearing comfort, affecting the application of far-infrared materials in glasses. Therefore, the present invention provides a high far-infrared glasses frame and a manufacturing method thereof to solve the above problems. Summary of the invention

[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a high far-infrared eyeglass frame and a manufacturing method thereof.

[0005] A high far infrared eyeglass frame consists of the following components, measured by mass: 75-94 parts of polyetheretherketone (PEEK), 5-20 parts of graphene, 1-5 parts of iron elements, and 0.5-2 parts of other auxiliary materials, wherein the iron element exists in the form of iron salt.

[0006] Furthermore, the iron salt includes one or more of ferric sulfate, ferrous sulfate, ferric chloride or other iron salts.

[0007] Furthermore, the other auxiliary materials include one or more of antioxidants, lubricants, plasticizers, and fillers.

[0008] Polyetheretherketone (PEEK) is used as the matrix material. PEEK has excellent mechanical properties, high temperature resistance and chemical stability, providing structural support and a durable foundation for the eyeglass frames. The addition of graphene nanoparticles can improve the thermal conductivity, electrical conductivity and mechanical strength of the material. In terms of far-infrared release, the broadband infrared emission characteristics of graphene help to enhance the far-infrared radiation capacity of the eyeglass frames. Iron salts in composite materials not only act as promoters of far-infrared radiation, but can also stimulate the release of far-infrared rays under specific conditions (such as temperature fluctuations) through changes in their electronic structure. In addition, iron ions have certain antibacterial properties. As an item in direct contact with the skin, the antibacterial properties of eyeglass frames can effectively reduce bacterial growth and protect eye health. The antibacterial mechanism of iron ions may involve processes such as destroying bacterial cell walls and interfering with bacterial metabolism.

[0009] A method for manufacturing a high-infrared far-infrared eyeglass frame comprises the following steps:

[0010] (1) Material preparation: converting graphene into nanoparticles by physical or chemical methods; preparing an iron salt solution; selecting high-quality polyetheretherketone as the matrix material;

[0011] (2) Mixing treatment: In a dehumidified environment, the graphene nanoparticles are mixed with the iron salt solution and stirred for at least 8 hours to obtain graphene-iron nanoparticles;

[0012] (3) Composite with polyetheretherketone: The uniformly mixed graphene-iron nanoparticles and polyetheretherketone are placed in a high-temperature melting device for heating and melting, the heating temperature is within the melting temperature range of 340-380° C., and the components are fully fused by melt blending to obtain a composite material;

[0013] (4) Granulation: The molten composite material is formed into a rod shape by an extruder or injection molding machine at an extrusion pressure of 50-150 MPa and a temperature consistent with the melting temperature, and then cut into particles of 2-5 mm in size;

[0014] (5) Injection molding: using a glasses frame mold to injection mold the particles into the shape of a glasses frame, setting the drying temperature to 150-160°C, the drying time to 3-4h, the processing temperature to 360-400°C, the mold temperature to 150-180°C, and cooling and demolding to obtain a high far-infrared glasses frame finished product;

[0015] (6) Surface treatment and coloring: The injection molded eyeglass frames are sprayed with primer, color layer and surface coating.

[0016] Furthermore, in the mixing step, the relative humidity of the dehumidified environment is controlled at 30%-50%, the stirring time is 8-12h, and the stirring speed is 50-100rpm.

[0017] Furthermore, the mixing step also includes nano-particle processing, that is, the mixture is nano-particleized by ultrasonic treatment or mechanical ball milling.

[0018] Furthermore, in the step of compounding with polyetheretherketone, the stirring speed of the melt blending process is 50-150 rpm and the melting time is 2-4 hours.

[0019] Furthermore, in the surface treatment and coloring steps, the primer is sprayed and then dried at 50-70°C for 20-40 minutes, the color coating is sprayed and then dried at 50-70°C for 2-3 hours, and the primer spraying and drying steps are repeated, and finally the surface coating is sprayed and dried at 50-70°C for 3-5 hours.

[0020] Furthermore, the surface treatment and coloring step also includes introducing nanometer-scale inorganic or organic materials into the surface coating, including one or more of nanometer silicon dioxide, nanometer aluminum oxide or fluorine-containing polymers.

[0021] Furthermore, the step of compounding with polyetheretherketone also includes adding 5-10% of the mass of the mixture into reinforcing fibers during the melt blending process, including one or more of carbon fiber, glass fiber or aramid fiber.

[0022] In the mixing step, graphene and iron salt are converted into nanoparticles by ultrasonic treatment or mechanical ball milling, which increases the specific surface area and surface activity of the material, promotes the interaction and uniform distribution between the components, and thus improves the overall performance of the composite material. Long-term stirring in a dehumidified environment ensures that the graphene nanoparticles and the iron salt solution are fully mixed to form uniform graphene-iron nanoparticles, laying a good foundation for the subsequent composite with polyetheretherketone.

[0023] In the step of compounding with polyetheretherketone, polyetheretherketone is heated to a molten state within an appropriate temperature range (340-380°C) and melt-blended with graphene-iron nanoparticles. During this process, the components are fully fused under stirring to form a composite material with excellent performance. Adding reinforcing fibers (such as carbon fibers, glass fibers, etc.) during the melt blending process can further improve the strength and toughness of the composite material while maintaining its lightweight characteristics.

[0024] During the injection molding step, the injection molding process parameters (drying temperature, processing temperature, mold temperature, etc.) are precisely controlled to ensure that the composite material particles flow evenly in the mold and quickly cool and solidify to form an eyeglass frame with precise size and shape.

[0025] Far-infrared release mechanism: The synergistic effect of graphene and iron elements enables the composite material to release far-infrared rays that are beneficial to the human body at room temperature. The release of far-infrared rays mainly comes from the vibration of the microstructure inside the material and the electron transition. These processes are affected by many factors such as temperature and electromagnetic field. When the human body wears high-infrared glasses frames, the far-infrared rays released by the glasses frames can penetrate the surface of the skin. Far-infrared radiation has a certain thermal effect on the human body, promoting cell metabolism and improving blood circulation, thereby achieving health effects such as relieving muscle tension and relieving fatigue.

[0026] The beneficial effects achieved by the present invention are as follows: 1. The present invention adopts polyetheretherketone (PEEK) as a matrix material, and utilizes the excellent properties of graphene, combined with the far-infrared emission enhancement effect of iron, to achieve stable far-infrared release; through a specific manufacturing method, including mixing graphene and iron, nano-particle treatment, and compounding with PEEK material, to achieve uniform distribution of far-infrared material in the eyeglass frame, and maintain the lightness and durability of PEEK material, and improve far-infrared emission performance, promote the wearer's local blood circulation and metabolism around the eye.

[0027] 2. The present invention nano-sizes graphene far-infrared materials and mixes them with a PEEK substrate to provide the eyeglass frame with excellent mechanical properties and processing properties. Through injection molding technology, a far-infrared eyeglass frame that is both lightweight and flexible is manufactured, which not only achieves a high far-infrared release rate, but also does not require electronic heating, achieving non-thermal release. Compared with traditional glasses, it is lighter and more flexible, providing a healthier and more comfortable wearing experience. At the same time, it has good impact resistance and wear resistance, thereby extending the service life of the product.

[0028] 3. The graphene, iron ions and PEEK used in the present invention are all non-toxic and harmless materials. After special treatment, they will not cause allergic reactions or adverse stimulation when in contact with human skin, so that the eyeglass frame has good biocompatibility and safety and is suitable for long-term wear.

[0029] 4. The present invention processes graphene and iron ions into nanoparticles and compounds them with PEEK materials through high-temperature melt blending technology to achieve a close combination of far-infrared materials and matrix materials, which not only improves product performance, but also simplifies the production process and reduces production costs.

[0030] 5. The high far-infrared glasses frame of the present invention is not only suitable for daily wear, but also can be used in specific fields, such as eye care, sports recovery, etc. Its unique far-infrared emission performance provides new solutions for these fields and has broad market prospects and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic flow chart of a method for manufacturing a high-infrared far-infrared eyeglass frame used in an embodiment of the present invention;

[0032] Figure 2 The far-infrared emissivity performance test results of the high far-infrared eyeglass frame used in the embodiment of the present invention;

[0033] Figure 3 The weight and toughness performance test results of the high far infrared glasses frame used in the embodiment of the present invention;

[0034] Figure 4 These are the durability performance test results of the high far-infrared eyeglass frame used in the embodiments of the present invention. DETAILED DESCRIPTION

[0035] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0036] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are for describing specific embodiments rather than for limiting the scope of protection of the present invention.

[0037] When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs.

[0038] The raw materials used in the following examples, unless otherwise specified, are all common commercially available products.

[0039] In the following embodiments, graphene is converted into nanoparticles by physical or chemical methods in the material preparation step. The physical methods include conventional ball milling and ultrasonic dispersion, and the chemical methods include chemical exfoliation combined with reduction, chemical vapor deposition post-treatment, and solution phase chemical cutting. Specifically, the physical method used in Examples 1 to 4 represents ball milling, and the chemical method represents chemical exfoliation combined with reduction.

[0040] In addition, the base oil is mainly composed of resin, solvent and a small amount of additives, and does not contain pigment; the color layer is a mixture of selected pigments and resin; the surface layer uses high-performance UV curing paint.

[0041] Example 1: A high far-infrared eyeglass frame, composed of the following components, by mass: 85 parts of polyetheretherketone (PEEK), 12 parts of graphene, 3 parts of iron, and 1 part of other auxiliary materials (including antioxidants and lubricants), wherein the iron exists in the form of iron salt (using a mixture of iron sulfate and iron chloride in a ratio of 1:1).

[0042] A method for manufacturing a high far infrared glasses frame, such as Figure 1 As shown, the following steps are included:

[0043] (1) Material preparation: convert graphene into nanoparticles by physical methods; prepare iron salt solution; select high-quality polyetheretherketone as the matrix material;

[0044] (2) Mixing treatment: In a dehumidified environment, the relative humidity is controlled at 40%, and the graphene nanoparticles and the iron salt solution are mixed uniformly, the stirring time is 10 hours, and the stirring speed is 75 rpm. During this period, the mixture is nano-particleized by ultrasonic treatment to obtain graphene-iron nanoparticles;

[0045] (3) Composite with polyetheretherketone: The uniformly mixed graphene-iron nanoparticles and polyetheretherketone are placed in a high-temperature melting device for heating and melting. The heating temperature is 360°C. Under the melting temperature, the components are fully fused by melt blending. The stirring speed of the melt blending process is 100 rpm. The melting time is 3 hours. During the melt blending process, 7% of the mass of reinforcing fiber (carbon fiber) is added to the mixture to obtain a composite material.

[0046] (4) Granulation: The molten composite material is formed into a rod shape by an extruder at an extrusion pressure of 100 MPa and a temperature consistent with the melting temperature, and then cut into particles of 3 mm in size;

[0047] (5) Injection molding: using a glasses frame mold to injection mold the particles into the shape of a glasses frame, setting the drying temperature to 155°C, the drying time to 3.5 h, the processing temperature to 380°C, the mold temperature to 165°C, and cooling and demolding to obtain a high far-infrared glasses frame finished product;

[0048] (6) Surface treatment and coloring: The injection molded eyeglass frames are subjected to primer spraying, color layer spraying and surface coating spraying. After the primer spraying, the frames are dried at 60°C for 30 minutes. After the color coating is sprayed, the frames are dried at 60°C for 2.5 hours. The primer spraying and drying steps are repeated. Finally, the surface coating is sprayed and dried at 60°C for 4 hours.

[0049] Example 2: A high far-infrared eyeglass frame, composed of the following components, by mass: 78 parts of polyetheretherketone (PEEK), 18 parts of graphene, 4.5 parts of iron, and 1.8 parts of other auxiliary materials (including antioxidants, lubricants and plasticizers), wherein the iron exists in the form of iron salt (using ferrous sulfate).

[0050] A method for manufacturing a high far infrared glasses frame, such as Figure 1 As shown, the following steps are included:

[0051] (1) Material preparation: convert graphene into nanoparticles by chemical methods; prepare iron salt solution; select high-quality polyetheretherketone as the matrix material;

[0052] (2) Mixing treatment: In a dehumidified environment, the relative humidity is controlled at 30%, and the graphene nanoparticles and the iron salt solution are mixed evenly, the stirring time is 8 hours, and the stirring speed is 50 rpm. During this period, the mixture is nano-particleized by a mechanical ball milling method to obtain graphene-iron nanoparticles;

[0053] (3) Composite with polyetheretherketone: The uniformly mixed graphene-iron nanoparticles and polyetheretherketone are placed in a high-temperature melting device for heating and melting. The heating temperature is 340°C. Under the melting temperature, the components are fully fused by melt blending. The stirring speed of the melt blending process is 50 rpm, and the melting time is 2 h. During the melt blending process, reinforcing fibers (glass fibers) of 9% by mass of the mixture are added to obtain a composite material.

[0054] (4) Granulation: The molten composite material is formed into a rod shape by an injection molding machine, with an extrusion pressure of 50 MPa and a temperature consistent with the melting temperature, and then cut into particles with a size of 2 mm;

[0055] (5) Injection molding: using a glasses frame mold to injection mold the particles into the shape of a glasses frame, setting the drying temperature to 150°C, the drying time to 3 hours, the processing temperature to 360°C, the mold temperature to 150°C, and cooling and demolding to obtain a high far-infrared glasses frame finished product;

[0056] (6) Surface treatment and coloring: The injection molded eyeglass frames are subjected to primer spraying, color layer spraying and surface coating spraying. After the primer spraying, the frames are dried at 50°C for 20 minutes. After the color coating is sprayed, the frames are dried at 60°C for 2 hours. The primer spraying and drying steps are repeated. Finally, the surface coating is sprayed and dried at 50°C for 3 hours.

[0057] Example 3: A high far-infrared eyeglass frame, composed of the following components, by mass: 92 parts of polyetheretherketone (PEEK), 8 parts of graphene, 1.5 parts of iron, and 0.7 parts of other auxiliary materials (including antioxidants and lubricants), wherein the iron exists in the form of iron salt (using a mixture of iron sulfate and iron chloride in a ratio of 1:1).

[0058] A method for manufacturing a high far infrared glasses frame, such as Figure 1 As shown, the following steps are included:

[0059] (1) Material preparation: converting graphene into nanoparticles by physical methods; preparing an iron salt solution; selecting high-quality polyetheretherketone as the matrix material;

[0060] (2) Mixing treatment: In a dehumidified environment, the relative humidity is controlled at 50%, and the graphene nanoparticles and the iron salt solution are mixed uniformly, the stirring time is 12 hours, and the stirring speed is 100 rpm. During this period, the mixture is nano-particleized by ultrasonic treatment to obtain graphene-iron nanoparticles;

[0061] (3) Composite with polyetheretherketone: The uniformly mixed graphene-iron nanoparticles and polyetheretherketone are placed in a high-temperature melting device for heating and melting. The heating temperature is 380°C. Under the melting temperature, the components are fully fused by melt blending. The stirring speed of the melt blending process is 150 rpm. The melting time is 4 hours. During the melt blending process, 5% of the mass of the mixture is added with reinforcing fiber (aramid fiber) to obtain a composite material.

[0062] (4) Granulation: The molten composite material is formed into a rod shape by an extruder at an extrusion pressure of 150 MPa and a temperature consistent with the melting temperature, and then cut into particles of 4 mm in size;

[0063] (5) Injection molding: using a glasses frame mold to injection mold the particles into the shape of a glasses frame, setting the drying temperature to 160°C, the drying time to 4 hours, the processing temperature to 400°C, the mold temperature to 180°C, and cooling and demolding to obtain a high far-infrared glasses frame finished product;

[0064] (6) Surface treatment and coloring: The injection molded eyeglass frames are subjected to primer spraying, color layer spraying and surface coating spraying. After the primer spraying, the frames are dried at 70°C for 40 minutes. After the color coating is sprayed, the frames are dried at 70°C for 3 hours. The primer spraying and drying steps are repeated. Finally, the surface coating is sprayed and dried at 70°C for 5 hours.

[0065] Example 4: A high far-infrared eyeglass frame, composed of the following components, by mass: 94 parts of polyetheretherketone (PEEK), 6 parts of graphene, 2 parts of iron, and 0.5 parts of other auxiliary materials (including plasticizers), wherein the iron exists in the form of iron salt (using ferric chloride).

[0066] A method for manufacturing a high far infrared glasses frame, such as Figure 1 As shown, the following steps are included:

[0067] (1) Material preparation: convert graphene into nanoparticles by chemical methods; prepare iron salt solution; select high-quality polyetheretherketone as the matrix material;

[0068] (2) Mixing treatment: In a dehumidified environment, the relative humidity is controlled at 45%, and the graphene nanoparticles and the iron salt solution are mixed uniformly, the stirring time is 9 hours, and the stirring speed is 80 rpm. During this period, the mixture is nano-particleized by a mechanical ball milling method to obtain graphene-iron nanoparticles;

[0069] (3) Composite with polyetheretherketone: The uniformly mixed graphene-iron nanoparticles and polyetheretherketone are placed in a high-temperature melting device for heating and melting. The heating temperature is 350° C. Under the melting temperature, the components are fully fused by melt blending. The stirring speed of the melt blending process is 120 rpm, and the melting time is 3.5 h. During the melt blending process, 6% of reinforcing fiber (carbon fiber and glass fiber mixed in a ratio of 1:1) of the mixture is added to obtain a composite material;

[0070] (4) Granulation: The molten composite material is formed into a rod shape by an extruder at an extrusion pressure of 120 MPa and a temperature consistent with the melting temperature, and then cut into particles of 3.5 mm in size;

[0071] (5) Injection molding: using a glasses frame mold to injection mold the particles into the shape of a glasses frame, setting the drying temperature to 158°C, the drying time to 3.8 h, the processing temperature to 370°C, the mold temperature to 170°C, and cooling and demolding to obtain a high far-infrared glasses frame finished product;

[0072] (6) Surface treatment and coloring: The injection molded eyeglass frames are subjected to primer spraying, color layer spraying and surface coating spraying. After the primer spraying, the frames are dried at 65°C for 35 minutes. After the color coating is sprayed, the frames are dried at 65°C for 2.8 hours. The primer spraying and drying steps are repeated. Finally, the surface coating is sprayed and dried at 65°C for 4.5 hours.

[0073] Comparative example: An ordinary PA12 eyeglass frame is composed of the following ingredients, calculated by mass: 94 parts of polyamide 12 (PA12), 3 parts of glass fiber, 0.5 parts of antioxidant, 0.5 parts of light stabilizer, and 1 part of zinc stearate (lubricant).

[0074] The manufacturing method of ordinary PA12 eyeglass frames includes the following steps:

[0075] (1) PA12 resin, additives, etc. are accurately weighed and mixed according to the formula ratio, and the mixed raw materials are dried at 80° C. for 5 h;

[0076] (2) Add the dried raw material into the hopper of the injection molding machine, melt the raw material into a viscous flow state by rotating and heating the screw, inject the molten PA12 into the mold (the same mold as in Example 1) at an injection pressure of 100 MPa and a temperature of 360° C., and ensure that the material is fully solidified and formed; after cooling, open the mold and take out the finished PA12 eyeglass frame;

[0077] (3) Trimming the injection molded eyeglass frames, including removing burrs, flash and other defects, and performing surface treatments such as grinding and polishing as needed.

[0078] (4) Finally, the eyeglass frame is subjected to primer spraying, color layer spraying and surface coating spraying. After the primer spraying, the frame is dried at 60°C for 30 minutes. After the color coating is sprayed, the frame is dried at 60°C for 2.5 hours. The primer spraying and drying steps are repeated. Finally, the surface coating is sprayed and dried at 60°C for 4 hours.

[0079] Performance test: The eyeglass frames prepared in Examples 1 to 4 and the comparative example were tested for far infrared emissivity, weight, toughness, and durability;

[0080] 1. Far infrared emissivity test: Use a far infrared emissivity tester (FTIR spectrometer or dedicated far infrared emissivity meter), place the glasses frame to be tested in the test room, ensure that the ambient temperature is stable, use the far infrared emissivity tester to aim at the surface of the glasses frame, record its far infrared radiation intensity within a specific wavelength range, calculate the far infrared emissivity of the glasses frame according to the standard or reference sample provided by the instrument, repeat the test several times, and take the average value of the results. The test standard is that the far infrared emissivity should reach more than 90%, indicating that the glasses frame has good far infrared radiation performance.

[0081] 2. Weight test: Use a high-precision electronic scale (accuracy of 0.1g), place the electronic scale on a stable surface, and calibrate it to zero. Gently place the glasses frame to be tested on the electronic scale, record the displayed weight, repeat the measurement multiple times, and take the average value to reduce the error. Directly compare the weight of the glasses frames of each embodiment and the comparative example to evaluate the lightweight effect.

[0082] 3. Toughness test: Use a three-point bending test and a universal material testing machine. Design appropriate fixtures and support points according to the shape and size of the eyeglass frame. Fix the eyeglass frame on the testing machine to ensure that the loading point is located at the appropriate position of the eyeglass frame (the connection between the temple and the frame). Apply bending force at a constant speed until the eyeglass frame is significantly deformed or broken. Record the maximum bending force and deformation. Evaluate the toughness of the eyeglass frame by comparing the maximum bending force and deformation. Larger bending force and deformation indicate that the eyeglass frame has better toughness.

[0083] 4. Durability test: including artificial sweat test, coating adhesion test, material corrosion resistance test, with a total score of 10 points for comprehensive scoring;

[0084] Artificial sweat test: a. Prepare artificial sweat that meets the standards. b. Immerse the eyeglass frame completely in the artificial sweat and place it in a constant temperature and humidity chamber, set a certain temperature (37°C) and humidity (95%), and keep it for a certain period of time (24 hours).

[0085] c. Take out the glasses frame, rinse it with clean water and let it dry naturally. d. Check if the coating on the glasses frame is peeling, discolored or corroded.

[0086] Coating adhesion test (scratch test or tape peel test):

[0087] a. Use a scratch tester to apply a certain amount of pressure on the coating surface and scratch it to observe whether the coating peels off.

[0088] b. Or use tape to stick on the coating surface and quickly tear it off to observe whether the coating falls off with the tape.

[0089] Material corrosion resistance test:

[0090] a. Observe the overall shape changes of the eyeglass frame after the artificial sweat test to see if there are any cracks, deformation, etc.

[0091] b. Use a microscope to observe the microstructural changes on the material surface and evaluate the corrosion resistance of the material.

[0092] Evaluation criteria: After the artificial sweat test, the eyeglass frames should show no obvious coating shedding, discoloration or corrosion.

[0093] Coating adhesion testing should show good bonding between the coating and the substrate.

[0094] Material corrosion resistance testing should show that the eyeglass frames can maintain good shape and performance in harsh environments.

[0095] from Figure 2 It can be seen that the high far-infrared eyeglass frames prepared in Examples 1 to 4 exhibit relatively high far-infrared emissivity, all of which are above 90%, indicating that far-infrared rays can be continuously released without external heating or electronic equipment; Figure 3 It can be seen that the eyeglass frames of the three embodiments are about 10% lighter than ordinary PA12 glasses, reflecting the advantages of lightweight design, and they all performed well in the toughness test, being able to withstand large bending forces without breaking easily, thus improving wearing comfort; according to the durability test results, Figure 4 It can be seen that the eyeglass frames of all embodiments show high durability, good adhesion and material corrosion resistance.

[0096] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A high far infrared glasses frame, characterized in that: The invention is composed of the following ingredients by weight: 75-94 parts of polyetheretherketone, 5-20 parts of graphene, 1-5 parts of iron element and 0.5-2 parts of other auxiliary materials, wherein the iron element exists in the form of iron salt.

2. A high far infrared glasses frame according to claim 1, characterized in that: The iron salt includes one or more of ferric sulfate, ferrous sulfate, ferric chloride or other iron salts.

3. A high far infrared glasses frame according to claim 1, characterized in that: The other auxiliary materials include one or more of antioxidants, lubricants, plasticizers, and fillers.

4. The method for manufacturing a high-infrared far-infrared eyeglass frame according to claim 1, characterized in that: The following steps are involved: (1) Material preparation: converting graphene into nanoparticles by physical or chemical methods; Prepare iron salt solution; select high-quality polyetheretherketone as the matrix material; (2) Mixing treatment: In a dehumidified environment, the graphene nanoparticles are mixed with the iron salt solution and stirred for at least 8 hours to obtain graphene-iron nanoparticles; (3) Composite with polyetheretherketone: The uniformly mixed graphene-iron nanoparticles and polyetheretherketone are placed in a high-temperature melting device for heating and melting, the heating temperature is within the melting temperature range of 340-380° C., and the components are fully fused by melt blending to obtain a composite material; (4) Granulation: The molten composite material is formed into a rod shape by an extruder or injection molding machine at an extrusion pressure of 50-150 MPa and a temperature consistent with the melting temperature, and then cut into particles of 2-5 mm in size; (5) Injection molding: using a glasses frame mold to injection mold the particles into the shape of a glasses frame, setting the drying temperature to 150-160°C, the drying time to 3-4h, the processing temperature to 360-400°C, the mold temperature to 150-180°C, and cooling and demolding to obtain a high far-infrared glasses frame finished product; (6) Surface treatment and coloring: The injection molded eyeglass frames are sprayed with primer, color layer and surface coating.

5. The method for manufacturing a high-infrared far-infrared eyeglass frame according to claim 4, characterized in that: In the mixing step, the relative humidity of the dehumidified environment is controlled at 30%-50%, the stirring time is 8-12 hours, and the stirring speed is 50-100 rpm.

6. The method for manufacturing a high-infrared far-infrared eyeglass frame according to claim 4, characterized in that: The mixing step also includes nanoparticle processing, that is, the mixture is nanoparticleized by ultrasonic treatment or mechanical ball milling.

7. The method for manufacturing a high-infrared far-infrared eyeglass frame according to claim 4, characterized in that: In the step of compounding with polyetheretherketone, the stirring speed during the melt blending process is 50-150rpm, and the melting time is 2-4h.

8. The method for manufacturing a high-infrared far-infrared eyeglass frame according to claim 4, characterized in that: In the surface treatment and coloring step, the primer is sprayed and then dried at 50-70°C for 20-40 minutes, the color coating is sprayed and then dried at 50-70°C for 2-3 hours, and the primer spraying and drying steps are repeated. Finally, the surface coating is sprayed and dried at 50-70°C for 3-5 hours.

9. The method for manufacturing a high-infrared far-infrared eyeglass frame according to claim 4, characterized in that: The surface treatment and coloring step also includes introducing nanometer-scale inorganic or organic materials into the surface coating, including one or more of nanometer silicon dioxide, nanometer aluminum oxide or fluorine-containing polymer.

10. The method for manufacturing a high-infrared far-infrared eyeglass frame according to claim 4, characterized in that: The step of compounding with polyetheretherketone also includes adding 5-10% of the mass of the mixture of reinforcing fibers during the melt blending process, including one or more of carbon fiber, glass fiber or aramid fiber.